1983
DOI: 10.1002/jcp.1041160204
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for monovalent phosphate transport in Ehrlich ascites tumor cells

Abstract: In an effort to determine whether the Na+-dependent Pi transport system of Ehrlich ascites tumor cells exhibits specificity for H2PO4- or HPO4(-2), Pi fluxes were determined by measuring 32Pi-Pi self-exchange. Three experimental approaches were employed. First, the effect of pH on steady-state Pi transport at 0.5 and 5 mM was studied. Second, the relationship between Pi transport and Pi concentration (0.25-9.2 mM) at pH 5.6 and 7.9 was determined. Third, the dependence of Pi transport on [H2PO4-] (0.05-4.2 mM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Studies have now been initiated on P~ transport processes in heart and skeletal muscle (Nuutinen & Hassinen, 1981;Medina & Illingsworth, 1980), nerve fibers (Jirounek et al, 1982(Jirounek et al, , 1984, across the placenta (Stulc & Stulcova, 1984;Brunette & Allard, 1985), and in a variety of cultured cell lines. In addition, uptake of P~ by cancer cells has been studied (Wehrle & Pedersen, 1982;Bowen & Levinson, 1983), partly to determine whether Pi uptake plays a role in rapid growth. A derepressible, sodium-dependent, high-affinity Pi transport system is also found in yeast (Roomans, Blasco & Borst-Pauwels, 1977).…”
Section: H+/pi Cotransport In Higher Plants Appears To Include a Highmentioning
confidence: 99%
“…Studies have now been initiated on P~ transport processes in heart and skeletal muscle (Nuutinen & Hassinen, 1981;Medina & Illingsworth, 1980), nerve fibers (Jirounek et al, 1982(Jirounek et al, , 1984, across the placenta (Stulc & Stulcova, 1984;Brunette & Allard, 1985), and in a variety of cultured cell lines. In addition, uptake of P~ by cancer cells has been studied (Wehrle & Pedersen, 1982;Bowen & Levinson, 1983), partly to determine whether Pi uptake plays a role in rapid growth. A derepressible, sodium-dependent, high-affinity Pi transport system is also found in yeast (Roomans, Blasco & Borst-Pauwels, 1977).…”
Section: H+/pi Cotransport In Higher Plants Appears To Include a Highmentioning
confidence: 99%
“…The time-dependent decrease in pHi shown in the upper curve of Figure 1 indicates that inhibition of Pi uptake was manifest when pHi reached a value below about 6.5. The rate of Pi transport during the 15-to 25-minute period following the change in pHo corresponds closely to the P i flux in cells equilibrated at pHo 5.5 (Bowen and Levinson, 1983). Clearly, the rapid decrease of pHo does not result in the inhibition of Pi transport.…”
Section: Resultsmentioning
confidence: 85%
“…Previous studies of the effect of pH on Pi transport (Bowen and Levinson, 1983) showed that the maximal rate of transport, which occurs at pHo 6.9, is inhibited by both a n increase and a decrease in H f concentration. These results were obtained only when cells were equilibrated at pHo between 5.5 and 7.9.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The extracellular space containing trapped [14C]-DMO was estimated to be 21% of the total volume of the centrifuged cell pellet. This value was obtained from measurements using [32p] p~ or [3H]-methoxyinulin as extracellular space markers (Bowen & Levinson, 1983). The appropriate correction was applied to the intracellular [14C]-DMO radioactivity and the ratio (cpm/ml cell water)/(cpm/ml medium) was calculated.…”
Section: Intracellular Phmentioning
confidence: 99%